Randomised clinical trial: oral taurine supplementation versus placebo reduces muscle cramps in patients with chronic liver disease. Issue 7 (23rd August 2018) - Vidot, Helen; Cvejic, Erin; Carey, Sharon; Strasser, Simone Irene; McCaughan, Geoffrey William; Allman‐Farinelli, Margaret; Shackel, Nicholas Adam
Summary: Background: Painful muscle cramps occur in the majority of patients with cirrhosis impacting significantly on quality of life and sleep patterns. They are frequently unrecognised or overlooked. Current management is based on anecdotal evidence or case study reports. Aim: To investigate the effect of oral taurine supplementation on frequency, duration, and intensity of muscle cramps in patients with chronic liver disease. Methods: Patients with chronic liver disease who experienced three or more muscle cramps/week were enrolled in a double‐blinded, randomised control, crossover, taurine dose‐variable study. Each participant received either taurine supplementation or placebo for 4 weeks then crossed to the alternative arm. Primary outcome data for frequency, duration, and intensity of muscle cramps was recorded by participants. Participants recorded frequency, duration, and location of muscle cramps. Biochemical parameters, including serum taurine and methionine levels, were measured at each time point. Linear mixed models were used to analyse outcomes. Results: Forty‐nine patients were enrolled in the study and 30 patients completed the protocol. Participants who were unable to complete the protocol were not included in the final analysis due to the absence of outcome data. The mean age of participants was 54.7 years and 70% were males. Oral taurine supplementation increased serum taurine levels ( P < 0.001). There were no adverse side effects associated with taurine supplementation. Participants receiving 2 g taurine/d experienced a reduction in cramp frequency (seven cramps fewer/fortnight, P = 0.03), duration (89 minutes less/fortnight P = 0.03), and severity (1.4 units less on a Likert scale P < 0.004) compared to placebo. Conclusions: Oral supplementation with 2 g taurine/d results in a clinically significant reduction in the frequency, duration, and intensity of muscle cramps in patients with chronic liver disease. Taurine should be considered as a safe and effective intervention in the management of muscle cramps in individuals with chronic liver disease. This study was registered with the Australian New Zealand Clinical Trials Register: ACTRN12612000289819.